2009
DOI: 10.1007/s11664-009-0846-8
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nitride Films Deposited by RF Sputtering for Microstructure Fabrication in MEMS

Abstract: In the present work, we report silicon nitride films deposited by a radiofrequency (RF) sputtering process at relatively low temperatures (<260°C) for microelectromechanical system (MEMS) applications. The films were prepared by RF diode sputtering using a 3-inch-diameter Si 3 N 4 target in an argon ambient at 5 mTorr to 20 mTorr pressure and an RF power of 100 W to 300 W. The influence of the film deposition parameters, such as RF power and sputtering pressure, on deposition rate, Si-N bonding, surface roughn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Moreover, the formation of the film is related with the condensing energy of the atoms (adatoms) on the surface of the substrate. Different works have found that amorphous films are formed when the adatoms have low energy of diffuse on the surface that does not allow that they may find low energy sites for the nucleation; while, a crystalline structure may be formed when the adatoms have a high surface mobility [8,15,[80][81][82][83][84][85][86][87][88]. However, several works have found that when the growing films are exposed to bombardment of high-energy particle, the structure and properties of deposited films can be improved.…”
Section: Growth Of Thin Films Using DC Reactive Magnetron Sputtering mentioning
confidence: 99%
“…Moreover, the formation of the film is related with the condensing energy of the atoms (adatoms) on the surface of the substrate. Different works have found that amorphous films are formed when the adatoms have low energy of diffuse on the surface that does not allow that they may find low energy sites for the nucleation; while, a crystalline structure may be formed when the adatoms have a high surface mobility [8,15,[80][81][82][83][84][85][86][87][88]. However, several works have found that when the growing films are exposed to bombardment of high-energy particle, the structure and properties of deposited films can be improved.…”
Section: Growth Of Thin Films Using DC Reactive Magnetron Sputtering mentioning
confidence: 99%
“…Some authors used this treatment to enable the attachment of monolayers directly to the silicon atoms. 22,82,83 However, the monolayers formed are not strictly self-assembled as they require UV induced coupling or elevated temperatures. [84][85][86] Another reason surface etching using HF is to reform an oxide layer with a consistent depth by controlling the immersion time in piranha.…”
Section: Factors Inuencing Sam Formationmentioning
confidence: 99%
“…Some authors used this treatment to enable the attachment of monolayers directly to the silicon atoms. 22,82,83 However, the monolayers formed are not strictly self-assembled as they require UV induced coupling or elevated temperatures.…”
mentioning
confidence: 99%
“…[5][6][7] For the tunnel passivated layer, SiO 2 is not the only option, and it has been confirmed that Si nitride (SiN x ) can also work well in passivated contact under appropriate conditions. 8) There are many methods to form thin tunnel SiN x films, such as sputtering, 9) jet vapor deposition, 10,11) atomic layer deposition, 12) plasma-enhanced chemical vapor deposition (PECVD), [13][14][15] and direct nitridation, 16,17) some of which have been conventionally used in the industry of semiconductor devices. 18,19) Of a variety of methods, catalytic CVD (Cat-CVD), often also referred to as hot-wire CVD, may be one of the best ways for the formation of thin tunnel SiN x .…”
Section: Introductionmentioning
confidence: 99%